Promoting the Effective Teaching and Learning of Social Studies through the Use of Mastery Learning Strategies in the 21st Century - Egharevba, John; Iyamu, E.O. S. (NIU Journal of Social Sciences; Vol 6 No 2 (2020): KIU Journal of Social Sciences, Vol. 6 No. 2, June 2020, 2020)
Social studies as a subject is of a fairly recent origin through the world. The subject deals with man’s interaction with his environment and how the environment equally influences man. Social studies as a discipline involve the teaching of values, norms and good attitude for the survival of the individual in the society. While interacting with his physical and social environment man encounter problems and challenges in his quest to live comfortably, orderly and meaningfully. Incidentally the programme of social studies in schools has been implemented for many years without success in terms of inculcating the right values of good citizenship among the youths. It is assumed that this deficiency arises from the way the subject is been taught and learnt in the classrooms. The study attempts to look at how social studies can be effectively taught in schools through master learning strategies and effective evaluation. We believe that if this study is properly followed and implemented, we are bound to achieve maximum learning of social studies in our schools.